Plastic additives alter the influence of photodegradation on biodegradation of polyethylene/polypropylene polymers in natural rivers - Niu, Lihua; Shen, Jiayan; Li, Yi; Chen, Yamei; Zhang, Wenlong; Wang, Longfei (Journal of hazardous materials, 2025)
The biodegradation of microplastics in river sediments was subject to the prior photodegradation in surface water and can be greatly affected by polymers and additives. However, the understanding of the effects of additives on the cascade photo- and biodegradation processes remains limited. In this study, the characteristics of morphology, functional groups, and indictive degrading bacteria of polyethylene (PE) and polypropylene (PP) were detected to analyze the effects of Dioctyl phthalate (DOP), Bisphenol A (BPA) and Benzotriazole (BTA), on the single and cascade photo- and biodegradation processes of PP/PE films (PP/PEP, PP/PEB, PP/PEPB). The results showed that photodegradation enhanced the biodegradation, by creating smaller fractions which induced the proliferation of new PP/PE-degrading bacteria (P-bacteria). Compared to the general PP/PE-degrading bacteria, P-bacteria displayed higher standard betweenness centrality and carbon metabolism. Among the three additives, DOP most obviously promoted photo- and biodegradation processes, followed by BPA. BTA inhibited the photodegradation to biodegradation by absorbing UV light. Overall, these findings provide insights into the nonnegligible joint influence of photodegradation and additives on the biodegradation of PP/PE resins in natural rivers. [Display omitted] •Photodegradation facilitated the biodegradation of PP/PE polymers.•Photodegradation-induced degrading bacteria merited the degradation of PP/PE polymers.•DOP and BPA accelerated the cascade photo- and biodegradation of PP/PE polymers.•BTA inhibited the enhancement effect of photodegradation on biodegradation of PP/PE.•PP and PE had different sensitivity to photo- and biodegradation processes.